The use of stable isotopes for authentication of gadoid fish species - Victoria Monteiro Oliveira, Emanuel Joaquim [UNESP]; Sant'Ana, Lea Silvia [UNESP]; Ducatti, Carlos [UNESP]; Denadai, Juliana Celia [UNESP]; de Souza Kruliski, Cibele Regina [UNESP] (Springer, 2011)
The rise of processed seafood in international trade has increased the feasibility of fish species substitution. Gadidae fish species are sold commercially as salted fish, and differences in price between fish of different species may lead to falsification. The present study addresses this falsification issue by attempting to discriminate among salted Atlantic cod and salted saithe using isotope ratio mass spectrometry (IRMS) as well as the stable isotope ratios of carbon (delta(13)C) and nitrogen (delta(15)N). delta(15)N in tissues with lower turnover rates (bone and skin) and in tissues with greater turnover rates (muscle) can be used to authenticate the species of salted fish samples when distinguishing between Atlantic cod and saithe.
Keywords: Traceability; Atlantic cod; Saithe; delta(15)N; delta(13)C